Obstetric Anal Sphincter Injuries (OASIs) in Israel: A Review of the Incidence and Risk Factors - Ginath, Shimon (Rambam Maimonides Med J, 2017)
Obstetric anal sphincter injuries (OASIs) following vaginal deliveries are the main reason for subsequent development of anal incontinence in women. The diagnosis of such tears is crucial for treating and preventing such a grave sequela. The reported rate of OASIs in Israel was between 0.1% and 0.6%, out of all vaginal births, which is 10-fold lower than that reported in Europe and the United States. Structured hands-on training in repair of OASIs in seven medical centers in Israel significantly increased the detection rate of third-degree perineal tears. The implementation of such programs is crucial for increasing awareness and detection rates of OASIs following vaginal deliveries.